Humor in contemporary junior literature - Cross, Julie, 1966- (Children's literature and culture ;, 2011)
In this new book, Julie Cross examines the intricacies of textual humor in contemporary junior literature, using the tools of literary criticism and humor theory. Cross investigates the dialectical paradoxes of humor and debunks the common belief in oppositional binaries of 'simple' versus 'complex' humor. The varied combinations of so-called high and low forms of humor within junior texts for young readers, who are at such a crucial stage of their reading and social development, provide a valuable commentary upon the culture and values of contemporary western society, making the book of consi.